2013
DOI: 10.1371/journal.pone.0070772
|View full text |Cite
|
Sign up to set email alerts
|

Low Glucose but Not Galactose Enhances Oxidative Mitochondrial Metabolism in C2C12 Myoblasts and Myotubes

Abstract: BackgroundSubstituting galactose for glucose in cell culture media has been suggested to enhance mitochondrial metabolism in a variety of cell lines. We studied the effects of carbohydrate availability on growth, differentiation and metabolism of C2C12 myoblasts and myotubes.Methodology/Principal FindingsWe measured growth rates, ability to differentiate, citrate synthase and respiratory chain activities and several parameters of mitochondrial respiration in C2C12 cells grown in media with varying carbohydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 28 publications
5
35
2
Order By: Relevance
“…We used both low and high glucose media to determine the effect of Nano on mitochondrial respiration. As previously reported [30], the presence of high glucose actually reduced mitochondrial respiration as evident from a reduction in basal respiration, maximal respiration, ATP production, and spare respiratory capacity (Fig. 9A).…”
Section: Resultssupporting
confidence: 87%
“…We used both low and high glucose media to determine the effect of Nano on mitochondrial respiration. As previously reported [30], the presence of high glucose actually reduced mitochondrial respiration as evident from a reduction in basal respiration, maximal respiration, ATP production, and spare respiratory capacity (Fig. 9A).…”
Section: Resultssupporting
confidence: 87%
“…As seen in Figure 2A, 2 H enrichment in DNA-derived deoxyribose and protein-derived alanine occurred rapidly, and while the absolute amount of labelling differed between the two molecules, the rate of rise in enrichment, referred to as the rise to plateau, was remarkably similar and occurred within 72 h. Accordingly, using non-linear least squares fitting of plots, the calculated DNA ( k = 0.044 h −1 ) and protein (0.043 h −1 ) turnover constants were very similar. The t 1/2 for protein, which represents the time taken to achieve 50% turnover, was 16.16 h. In the case of DNA labelling, the t 1/2 , which represents the cell doubling time, was calculated to be 15.69 h, which is consistent with previously published C2C12 doubling times of 15.2–19.7 h [49], as assessed using manual cell counting. The maximum level of 2 H-labeling in deoxyribose was higher than in alanine (Figure 2A), because there are more opportunities for 2 H to be incorporated into deoxyribose (through the pentose phosphate pathway, hexose phosphate isomerization) [35], compared to alanine (transamination of pyruvate) [30,31,32].…”
Section: Resultssupporting
confidence: 87%
“…Thus, the production of ATP in C2C12 cells may be highly dependent on the presence of glucose. To support this, a previous study demonstrated that C2C12 cells exhibited lower maximal respiration and drastic inhibition of proliferation under glucose‐free conditions (Elkalaf et al, ). In any case, USP2 may contribute to maintaining the supply of ATP in C2C12 cells in the presence of glucose.…”
Section: Discussionmentioning
confidence: 87%
“…In the present study, we demonstrated that USP2 contributes to the generation of sufficient ATP by OXPHOS in myoblasts. On the other hand, Usp2 KO cells exhibited impairments in proliferation and differentiation, both of which require an adequate glucose‐derived energy supply by the mitochondria (Elkalaf et al, ; Riddle et al, ). Collectively, these results suggest that USP2 might control proliferation and differentiation in myoblasts through sustained activation of mitochondria.…”
Section: Discussionmentioning
confidence: 99%